2020
DOI: 10.1111/bph.14926
|View full text |Cite
|
Sign up to set email alerts
|

PO‐322 exerts potent immunosuppressive effects in vitro and in vivo by selectively inhibiting SGK1 activity

Abstract: Background and Purpose Immunosuppressive drugs have shown great promise in treating autoimmune diseases in recent years. A series of novel oxazole derivatives were screened for their immunosuppressive activity. PO‐322 [1H‐indole‐2,3‐dione 3‐(1,3‐benzoxazol‐2‐ylhydrazone)] was identified as the most effective of these compounds. Here, we have investigated the mechanism(s) underlying the inhibition of T‐cell proliferation in vitro by PO‐322, as well as its effects on the delayed‐type hypersensitivity (DTH) respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In recent years, as one of the laboratories studying the role and function of SGK1 in human cancer, we identified SGK1 as a crucial key molecule involved in prostate cancer (PCa) progression through regulation of cell apoptosis, cell cycle, invasion/migration, and autophagy ( 19 , 20 ). The role of SGK1 in human cancer has been explored in numerous clinical, translational, and basic studies ( 6 , 11 , 12 ). An increasing amount of scientific evidence has confirmed the therapeutic potential of SGK1 in human cancer ( 11 ), and a critical review is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, as one of the laboratories studying the role and function of SGK1 in human cancer, we identified SGK1 as a crucial key molecule involved in prostate cancer (PCa) progression through regulation of cell apoptosis, cell cycle, invasion/migration, and autophagy ( 19 , 20 ). The role of SGK1 in human cancer has been explored in numerous clinical, translational, and basic studies ( 6 , 11 , 12 ). An increasing amount of scientific evidence has confirmed the therapeutic potential of SGK1 in human cancer ( 11 ), and a critical review is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SGK1 in human cancer has been explored in numerous clinical, translational, and basic studies ( 6 , 11 , 12 ). An increasing amount of scientific evidence has confirmed the therapeutic potential of SGK1 in human cancer ( 11 ), and a critical review is necessary. In this review, we focus on the diagnostic and prognostic value of SGK1 in human cancer, which has not yet been critically reviewed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.2.1 PO-322 (5) Lai et al (2020) identified PO-322 (5) as a selective SGK1 inhibitor that acts as an immunosuppressant. Initially, the authors examined the effects of in-house oxazole derivatives on T cell proliferation following anti-CD3 or anti-CD28 stimulation.…”
Section: Sgk1 Inhibitors As An Immune Modulatormentioning
confidence: 99%